PERANCANGAN PROTOTYPE APLIKASI TIKET WISATA DI KOTA PEMALANG MENGGUNAKAN UX LIFECYCLE - Khikma Mei Rida; Gita Fadila Fitriana; Darmansah Darmansah (LPPM Universitas Abdurrab, 2022)
Technology that continues to develop always provides new changes in improving the quality and performance of a company. Booking tourist tickets is one of the businesses that requiring the right information technology assistance. This business requires high mobility, fast information distribution, fast customer service, and real-time communication between branches or cities. Through this travel ticket application, users can find out the destination tourist locations in detail, order tickets online, and make ticket payments digitally to make it easier for tourists to make transactions. The data states that from 21 respondents, or 47.6% of the people of Pemalang city, they have difficulty when ordering tourist tickets in Pemalang City. Some people say that there are sometimes long queues in purchasing tickets, so it takes a long time, Difficulty in queuing when buying tourist tickets, especially on weekends, and too long queues make you lazy. So the author makes the design of the Prototype of the Travel Ticket application to make it easier for tourists to order tickets. The application prototype design process is carried out using the User Experience Lifecycle method. The design method is carried out using the wheel method initiated by Hartson and Pyla by paying attention to usability and user experience. This method has four stages, namely analysis, design, prototype, and evaluation. Usability testing on the Travel Ticket application is carried out using the System Usability Scale method..